Introduction to Computer Organization - Plantz, Robert (No Starch Press, 2022)
Introduction to Computer Organization gives programmers a practical understanding of what happens in a computer when you execute your code. You may never have to write x86-64 assembly language or design hardware yourself, but knowing how the hardware and software works will give you greater control and confidence over your coding decisions. We start with high level fundamental concepts like memory organization, binary logic, and data types and then explore how they are implemented at the assembly language level. The goal isn't to make you an assembly programmer, but to help you comprehend what happens behind the scenes between running your program and seeing "Hello World" displayed on the screen. Classroom-tested for over a decade, this book will demystify topics like: •How to translate a high-level language code into assembly language •How the operating system manages hardware resources with exceptions and interrupts •How data is encoded in memory •How hardware switches handle decimal data •How program code gets transformed into machine code the computer understands •How pieces of hardware like the CPU, input/output, and memory interact to make the entire system work.